Structure and mechanical properties of W incorporated diamond-like carbon films prepared by a hybrid ion beam deposition technique - Wang, Ai-Ying; Lee, Kwang-Ryeol; Ahn, Jae-Pyoung; Han, Jun Hee (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
W incorporated diamond-like carbon films were prepared on silicon(I 0 0) wafers using a hybrid deposition system composed of an end-Hall-type hydrocarbon ion gun and a tungsten DC magnetron sputter source. The W concentration in the films was controlled by changing the fraction of Ar in the Ar and C6H6 reaction gas. The chemical composition, atomic bond structure, and mechanical properties were investigated for W concentrations ranging from 0 to 8.6 at.%. When the W concentration was <2.8 at.%, the W atoms were dissolved in the amorphous carbon matrix without forming a WC1-x phase. Amorphous and crystalline WC1-x nano-particles appeared when the W concentration was >2.8 and >3.6 at.%, respectively. It was found that the hardness and elastic modulus were not sensitive to the W concentration in this concentration range. On the other hand, the residual compressive stress was strongly dependent on the chemical state of the incorporated W atoms. The change in mechanical properties is discussed in terms of the microstructural changes induced by W incorporation. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: NANOCOMPOSITE; MICROSTRUCTURE; SUPERHARD; COATINGS; STRESSES; HARDNESS